History and strategy - Kahl, Steven J.; Silverman, Brian S.; Cusumano, Michael A., 1954- (Advances in strategic management ;, 2012)
Business historians and economic historians frequently contribute to our understanding of strategic management, and strategy scholars often rely on a deep understanding of historical context to make sense of classic strategy issues. Historically, the two sets of scholars have not always communicated with each other as effectively as one might hope. They also have different approaches to methodology and assessment of validity of results, which adds to this 'two solitudes'. In this volume, strategy scholars, business historians, and economic historians are brought together to develop a volume that explores the complementarities of approaches.